The Potentials of an Integrated Ultrasonic Membrane Anaerobic System (IUMAS) in Treating Sugar Cane Wastewater - Abdurahman Hamid Nour; Yasmeen Hafiz Zaki; Hybat Salih Mohamed; Hesham Hussein Rassem (Universitas Gadjah Mada, 2019)
Excess levels of organic and inorganic matters in the discharge from sugarcane mill effluent (SCME) wastewater, causes the earnest environmental issue. In this study, a single unit integrated ultrasonic membrane anaerobic system (IUMAS) has been investigated for industrial sugarcane wastewater treatment. As the “Membrane-fouling” is one of the main constraints of IUMAS which eventually reduce the processing ability. In the present study, most researchers resort to cost reduction. IUMAS was alternatively applied as an economical approach for SCME wastewater treatment. The application of “Multiple-analysis” methods (COD, BOD, TSS) and three kinetic models during the treatment, suggested the specific range of organic loading rate to produce biogas. The result showed the increased methane gas production up to 80% in the biogas, with 94 -96% of COD removal efficiency from the SCME wastewater. Results concluded the effective efficiency of IUMAS to reduce the membrane fouling and treatment of SCME wastewater as well as enhanced production of methane gas.